Correlation Between Teachers' Years of Service Experience and Legal Literacy in Secondary Schools in Bobasi Sub-County, Kenya - Ominde, Eliud (Universal Education, 2026)
Legal literacy is a critical competency for teachers, which enables them to navigate complex school environments where legal obligations and risks frequently arise. Teachers often make decisions that affect the constitutional liberties of students, colleagues, and the broader school community. Despite this responsibility, various studies have shown that many teachers operate without formal legal training. This study investigated how gender, education level, and in-service experience influence legal literacy among secondary school teachers in Bobasi Sub-County, Kenya. A descriptive survey using a correlational research design was adopted. The target population included 395 secondary school teachers. Data were collected through structured questionnaires and analyzed using both descriptive and inferential statistics. Key findings show that gender has a statistically significant but weak influence on legal literacy, accounting for only 1.6% of the variance. Education level has a moderate influence, explaining 4.7% of the variance. In-service experience emerged as the strongest predictor, accounting for 31.2% of the variance in legal literacy. These findings suggest that practical experience is a key driver of legal knowledge, while gender plays a minor role. The study recommends integrating legal literacy into pre-service teacher training curricula and strengthening in-service professional development programs. Educational stakeholders should develop targeted legal education initiatives to bridge knowledge gaps and improve legal competency among teachers. Future research should explore additional factors such as access to legal resources, socioeconomic status, and cultural beliefs to gain a more comprehensive understanding of disparities in legal literacy.